2018
DOI: 10.1161/circep.118.006350
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Risk of Atrial Fibrillation by Race and Socioeconomic Status

Abstract: BACKGROUND:Limited information exists on the lifetime risk of atrial fibrillation (AF) in African Americans and by socioeconomic status. METHODS:We studied 15 343 participants without AF at baseline from the ARIC (Atherosclerosis Risk in Communities) cohort recruited in 1987 to 1989 from 4 communities in the United States when they were 45 to 64 years of age. Participants have been followed through 2014. Incidence rates of AF were calculated dividing the number of new cases by personyears of follow-up. Lifetim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
4
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 190 publications
(121 citation statements)
references
References 42 publications
2
112
4
3
Order By: Relevance
“…Several studies have shown a lower prevalence of AF in Asian people,12–14 and others have shown a lower rate in American-Africans 15. The work here does not rule out the contribution of genotypically driven/haplotype background-derived effects on the prevalence and architecture of AF in HF cases, however this is clearly not a definitive evidence base.…”
Section: Can the Research Show A Clear Rationale For The Differences contrasting
confidence: 62%
“…Several studies have shown a lower prevalence of AF in Asian people,12–14 and others have shown a lower rate in American-Africans 15. The work here does not rule out the contribution of genotypically driven/haplotype background-derived effects on the prevalence and architecture of AF in HF cases, however this is clearly not a definitive evidence base.…”
Section: Can the Research Show A Clear Rationale For The Differences contrasting
confidence: 62%
“…The causal pathway linking SEP to AF has not been thoroughly investigated and it may differ for education and income (see figure 4). There is no obvious direct biological mechanism for the observed association between low education and higher risk of AF 9 25–27. However, the association may be explained by intermediate variables.…”
Section: Discussionmentioning
confidence: 96%
“…The MB-LATER score good predictive ability for VLRAF could be partly explained by higher AF prevalence in men. 40,41…”
Section: Mb-latermentioning
confidence: 99%